Identification and Characterization of Novel Sources of Resistance to Rust Caused by Uromyces pisi in Pisum spp. - Salvador Osuna-Caballero; Nicolas Rispail; Eleonora Barilli; Diego Rubiales (Plants, 2022)
Pea rust is a major disease worldwide caused by Uromyces pisi in temperate climates. Only moderate levels of partial resistance against U. pisi have been identified so far in pea, urging for enlarging the levels of resistance available for breeding. Herein, we describe the responses to U. pisi of 320 Pisum spp. accessions, including cultivated pea and wild relatives, both under field and controlled conditions. Large variations for U. pisi infection response for most traits were observed between pea accessions under both field and controlled conditions, allowing the detection of genotypes with partial resistance. Simultaneous multi-trait indexes were applied to the datasets allowing the identification of partial resistance, particularly in accessions JI224, BGE004710, JI198, JI199, CGN10205, and CGN10206. Macroscopic observations were complemented with histological observations on the nine most resistant accessions and compared with three intermediates and three susceptible ones. This study confirmed that the reduced infection of resistant accessions was associated with smaller rust colonies due to a reduction in the number of haustoria and hyphal tips per colony. Additionally, a late acting hypersensitive response was identified for the first time in a pea accession (PI273209). These findings demonstrate that screening pea collections continues to be a necessary method in the search for complete resistance against U. pisi. In addition, the large phenotypic diversity contained in the studied collection will be useful for further association analysis and breeding perspectives.